DIGITAL TA'ARUF IN THE PERSPECTIVE OF THEMATIC HADITH: RECONSTRUCTING THE ETHICS OF CHOOSING A PARTNER IN THE ERA OF SOCIAL MEDIA - Muhamad Sulthon Amin Hakim; Ahmad Fudhaili (SOSIOEDUKASI, 2026)
The development of digital technology and social media has transformed the practice of ta'aruf among contemporary Muslims into a phenomenon known as digital ta'aruf. This shift changes the process of seeking prospective spouses from family- or community-mediated introductions toward digitally mediated interactions. Although digital ta'aruf provides wider access and efficiency, it also raises ethical challenges, including limited guardian (wali) supervision, identity misrepresentation, virtual khalwat, and interactions beyond Islamic boundaries. This study aims to examine digital ta'aruf through a thematic hadith approach (maudhu'i) by analyzing Prophetic traditions related to spouse selection, nazhar, the role of the wali, the prohibition of khalwat, and commitment ethics in marriage. This qualitative library research employs takhrij and sharh approaches to analyze relevant hadiths supported by contemporary literature on digital ta'aruf and Islamic ethics. The findings reveal five ethical principles underlying digital ta'aruf: prioritizing religion and morality in spouse selection, purposeful nazhar, maintaining ethical interaction boundaries, active guardian involvement, and commitment integrity. This study contributes a novel reconstruction of Hadith-Based Digital Ta'aruf Ethics through three dimensions: value orientation, interaction governance, and social accountability. The study concludes that digital ta'aruf can be accepted as a contemporary practice when technological convenience remains guided by Prophetic ethical principles.